Cassava : earning bread and butter - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
New food products from cassava. A Onabolu, A Abass & N Bokanga. 1998. 40 pp. US$ 10 Euro 10 (plus US$ 5 Euro 5 postage) International Institute of Tropical Agriculture PMB 5320, Oyo Road, Ibadan, Nigeria Fax: + 234 2 241 2221 Email: IITA@cgiar.